SEPTEMBER DAYS IN HALYCH IN 1939 – FORGOTTEN EPISODES. THE BEGINNING OF SECOND WORLD WAR AND THE OCCUPATION OF THE CITY BY THE RED ARMY - CHEMERYNSKYI, Andrii (Halych. Scientific work collection, 2024)
On August 23, 1939, a non-aggression pact was signed between Germany and the USSR (the Molotov-Ribbentrop Pact). A secret protocol was attached to the agreement. According to this protocol, the Soviet and German «spheres of influence» in Northern and Eastern Europe were defined. On September 1, 1939, World War II began – the Third Reich and the Slovak Republic launched a military operation against the Republic of Poland, and on September 17, the Soviet Union intervened in the conflict. The Red Army crossed the border of the Republic of Poland and began hostilities against the Polish army. At the local level, these events significantly affected and changed the lives of many settlements, including Halych. Until recently, this period of the city’s history was practically not covered, the issue was considered only through the prism of a new stage of urban life associated with the «liberation of the original Ukrainian lands by the Soviet Union» or «reunification of Western Ukraine with the Ukrainian SSR».